STRATEGI PENINGKATAN KESEJAHTERAAN DAN PEMBERDAYAAN KELUARGA PEKERJA MIGRAN (STUDI KASUS DI KABUPATEN JEMBER) - Fajar Wahyu Prianto; Achmad Bahri (Relawan Jurnal Indonesia, 2019)
Indonesia as a developing country with the largest participation, has contributed at this time. Economic motives are still the main interest of migrant workers. The purpose of this study is the variables that affect welfare and formulate strategies for empowering migrant worker families. Some of the variables hypothesized were Social Insurance, job training, household contributions to investment and human capital, and length of work experience. This research is an explanatory study using quantitative data with cluster random sampling methods and using interview techniques as research instruments. With the econometric method using OLS, the results showed that these variables have a significant relationship with statistics on the welfare of migrant workers' families ( = 0.05), both by partial and simultaneous tests. This model can also answer most explanations about the supported variables (R2 = 0.983). However, it also has implications for the strategy of empowering migrant worker families by encouraging their capacity in household investment, human capital, skills, experience, and labor social security.